Development of an Internet of Things-Based Soil Moisture Monitoring and Control System for Bird’s Eye Chili Cultivation Using Solar Energy - มาตะรักษ์ เรืองฤดี; แซ่หลิ่ม จิรายุ; ชื่นล้วน ระพีพล; ดีเจริญชิตพงศ์ จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: (1) design and develop an Internet of Things (IoT)-based soil moisture monitoring and control system for bird’s eye chili cultivation using solar energy, (2) test the system’s performance, and (3) assess user satisfaction. The system utilized an ESP32 microcontroller integrated with a soil moisture sensor and was controlled via the Blynk application using a threshold-based control approach. The results from a 7-day experiment in a potted bird’s eye chili cultivation context demonstrated that the system could continuously monitor and maintain soil moisture within the specified range, with 90% accuracy in water pump control and stable real-time display through the IoT platform. User satisfaction evaluated by 3 experts and users was at a high level (Mean = 4.27, S.D. = 0.31). Nevertheless, this study had limitations, including a relatively short experimental period and a limited number of evaluators. The researcher, therefore, suggests expanding the experimental scope and increasing the sample size in future research.